2,5-Dihydroxy-3-heptadecyl-1,4-benzoquinone and Stigmasterol from Heliotropium indicum L. - Hasan, Md Nazmul; Ahsan, Monira; Hasan, Choudhury Mahmood; Azam, ATM Zafrul (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Abstract not available Dhaka Univ. J. Pharm. Sci. 15(1): 113-115, 2016 (June)